Remaining Karen A Study of Cultural Reproduction and the Maintenance of Identity - Rajah, Ananda (ANU Press, 2008)
This publication of Remaining Karen is intended as a tribute to Ananda Raja and his consummate skills as an ethnographer. It is also a tribute to his long-term engagement in the study of the Karen. Remaining Karen was Ananda Raja's first focused study of the Sgaw Karen of Palokhi in northern Thailand, which he submitted in 1986 for this PhD in the Department of Anthropology in the Research School of Pacific and Asian Studies at The Australian National University. It is a work of superlative ethnography set in an historical and regional context and as such retains its value to the present.